(3TQM eHMK GdGSJUMGH ef aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg aj Odjdg Cj Odjd Pdc GdeQO bhdg hOYhi Gf KHhJ MGUd gPg GdOYhi Cf GdQhGjGJ GdePchQI JOd Ydi Cf GdehVhY ddeJfLS gh eWdb GdLSe hPdc dCf GdeQGOs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg dLedI eG PcQfG ef CNHGQ GdBMGO, Gj dCLd eG PcQfG aj HMK MLjI NHQ GdhGMO ef CNHGQ GdBMGO GdOGdI Ydi MLjI NHQ GdhGMO, bhdg hPcQfG JVYja Pdc Cj PcQfG aj HMK MLjI NHQ GdhGMO JVYja chf GdCUd aj NHQ GdYOd GdMLjIs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs